The relationship between water intake and the progression of urine albumin-creatinine ratio in patients with chronic kidney disease: A cohort-prospective study. - Yanti, Mulyanti Sulastri; RASYID, Haerani; AMINUDDIN, Aminuddin; AS'AD, Suryani; ASTUTI DAUD, Nurpudji; AINUN RANI, Nur (Nutrición Clínica y Dietética Hospitalaria, 2025)
Introduction: The urine albumin-creatinine ratio (uACR) is a key biomarker for assessing kidney function in patients with chronic kidney disease (CKD), with elevated levels indicating kidney damage. Water and protein metabolism significantly impact kidney function. Proper hydration influences vasopressin feedback and osmolality regulation, while excessive protein intake exacerbates kidney stress through hyperfiltration and increased urea production. This study aims to investigate the relationship between daily water and protein intake and uACR levels in CKD patients. Methods: A cohort study was conducted on 10 non-dialysis CKD patients at Dr. Wahidin Sudirohusodo Hospital, Makassar, Indonesia. Demographic and clinical data were collected, and average daily water and protein intake were assessed. The Spearman correlation test was used to analyze the relationship between water and protein intake and changes in uACR, albumin, and creatinine levels. Results: A strong negative correlation was found between daily water intake and uACR (ρ=-0.891, p=0.001), indicating that higher water consumption reduces uACR. Conversely, protein intake showed a strong positive correlation with uACR (ρ=0.770, p=0.009) and urine albumin levels (ρ=0.806, p=0.005), suggesting that higher protein consumption increases both uACR and albumin excretion. No significant correlation was found between water or protein intake and urine creatinine levels. Conclusion: This study highlights the importance of hydration and dietary protein regulation in managing CKD progression. Increased water intake may reduce uACR, while excessive protein intake can exacerbate kidney damage, emphasizing the need for dietary management in CKD patients.